2018
DOI: 10.3390/ncrna4040039
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Long Non-Coding RNA DRAIC Correlates with Adverse Features of Breast Cancer

Abstract: DRAIC (also known as LOC145837 and RP11-279F6.1), is a long non-coding RNA associated with several types of cancer including prostate cancer, lung cancer, and breast cancer. Its expression is elevated in tumor tissues compared to adjacent benign tissues in breast cancer patients and is regulated by estrogen treatment in breast cancer cells. In addition, expression analysis of DRAIC in more than 100 cell lines showed that DRAIC expression is high in luminal and basal subtypes compared to claudin low subtype, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…We identified the gene most specifically expressed among the cells in the same cluster for a total of 22 biomarkers, one for each cluster (Figure 2C and Supplementary Table 03 and Supplementary Figure 03). Literature mining confirmed prevalence and clinical relevance of the markers thus identified (Supplementary Table 03): for example, clusters in the luminal island (Figure 2C) were associated to genes involved in cancer progression (BCAS3 ( 28, 29 ) cluster 2), dissemination (SCGB2A2 ( 30, 31 ) cluster 6), proliferation (DRAIC ( 32, 33 ) cluster 1), migration and invasion (CLCA2 ( 34, 35 ) cluster 8 and PIP ( 36 ) cluster 18). Interestingly, whereas DRAIC is correlated with poorer survival of luminal BC patients ( 33 ), both CALCA2 and PIP are significantly associated with a favourable prognosis ( 34, 35, 37 ).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…We identified the gene most specifically expressed among the cells in the same cluster for a total of 22 biomarkers, one for each cluster (Figure 2C and Supplementary Table 03 and Supplementary Figure 03). Literature mining confirmed prevalence and clinical relevance of the markers thus identified (Supplementary Table 03): for example, clusters in the luminal island (Figure 2C) were associated to genes involved in cancer progression (BCAS3 ( 28, 29 ) cluster 2), dissemination (SCGB2A2 ( 30, 31 ) cluster 6), proliferation (DRAIC ( 32, 33 ) cluster 1), migration and invasion (CLCA2 ( 34, 35 ) cluster 8 and PIP ( 36 ) cluster 18). Interestingly, whereas DRAIC is correlated with poorer survival of luminal BC patients ( 33 ), both CALCA2 and PIP are significantly associated with a favourable prognosis ( 34, 35, 37 ).…”
Section: Resultsmentioning
confidence: 71%
“…Literature mining confirmed prevalence and clinical relevance of the markers thus identified (Supplementary Table 03): for example, clusters in the luminal island (Figure 2C) were associated to genes involved in cancer progression (BCAS3 (28, 29) cluster 2), dissemination (SCGB2A2 (30, 31) cluster 6), proliferation (DRAIC (32, 33) cluster 1), migration and invasion (CLCA2 (34, 35) cluster 8 and PIP (36) cluster 18). Interestingly, whereas DRAIC is correlated with poorer survival of luminal BC patients (33), both CALCA2 and PIP are significantly associated with a favourable prognosis (34,35,37). Indeed, CLCA2 was shown to be downregulated in several primary breast tumours, and loss of CLCA2 was associated with tumorigenicity and invasion potential (35,38) while overexpression showed decreased proliferative, migrating and invasive features (34).…”
Section: The Bc Single-cell Atlas Identifies Clinically Relevant Tranmentioning
confidence: 99%
“…Based on the differential expression of DRAIC in GC and NC tissues and its potential role in several malignant tumors [10][11][12][13][14][15][16][17], we decided to explore the relationship between DRAIC/ NFRKB and malignant phenotype of GC cells. It was found that DRAIC can restrain the proliferation abilities of HGC-27 and MKN45 cells ( Fig.…”
Section: Biological Effects Of Oedraic and Rescued By Oenfrkb On Gc Cmentioning
confidence: 99%
“…The lncRNA DRAIC gene, which is located on human chromosome 15q23, was reported as a novel tumor regulator in several cancers recently, but it seemed to exhibit different biological effects in cancer cells from different sources [10][11][12][13][14][15][16][17]. On account of the potential value of DRAIC as a GC marker and target, we intended to reveal the expression characteristics and precise mechanism of DRAIC.…”
Section: Biological Effects Of Shdraic On Gc Cellsmentioning
confidence: 99%
See 1 more Smart Citation